Exploring Sleep and Physical Activity among Young Adults Across Asia: A Systematic Literature Review - Tian, Vanida; Ramlee, Fatanah; Hamzah, Hazalizah; Ng, Teck Sen (Malaysian Journal of Medical Sciences, 2025)
Previous studies have examined the association between sleep and physical activity; however, few have systematically reviewed the studies on young adults in Asia. Therefore, the present study aimed to systematically summarise the research on sleep and physical activity among young adults in Asia and critically assess the methodological quality of existing studies. The review process adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines, beginning with research question formulation and systematic searches through identification, screening, and eligibility in the Scopus, PubMed, and ScienceDirect databases. Subsequently, the studies underwent quality appraisal, data extraction, and analysis. Thematic analysis organised the findings into three main themes: i) the prevalence of sleep quality and physical activity in Asia; ii) the association between sleep quality and physical activity; and iii) sleep quality and physical activity during the COVID-19 outbreak. These findings reveal a high prevalence of sleep deprivation and poor sleep quality among young adults in Asia, whereas the prevalence of physical activity varies. Moreover, the COVID-19 outbreak negatively affected sleep quality and physical activity. Therefore, proactive measures should be implemented to improve sleep quality and promote physical activity, thereby improving physical and mental health.